"And 1" More Piece of Evidence of Discrimination Against Black Basketball Players. Issue 3 (27th May 2019) - Dix, Andrew
Abstract: The main goal of the current research was to investigate the personal fouls that were called against female basketball players who play for historically Black colleges and universities (HBCUs). Extant scholarship has revealed that eclectic communication behaviors contextually persist on the campuses of HBCUs, whereas Black feminist thought was used as a theoretical frame for exploring biases against African American females. A series of statistical analyses were calculated on the personal fouls that transpired in the sport of women's college basketball from the 2008 through the 2017 season. The uncovered findings revealed that referees verbally called a disproportionate number of personal fouls on female basketball teams from HBCUs. Several female basketball teams from HBCUs incurred a personal fouls per game (PFPG) average that was significant at the .01 level but no female basketball teams from predominantly White institutions (PWIs) incurred a PFPG average that was significant at the .01 level. The discussion portion of this investigation went on to spotlight theoretical implications, White male hegemony, and overstated communication in sports.